2010
DOI: 10.2528/pier10071104
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Solutions of Metamaterial Problems Using a Low-Frequency Multilevel Fast Multipole Algorithm

Abstract: Abstract-We present fast and accurate solutions of electromagnetics problems involving realistic metamaterial structures using a lowfrequency multilevel fast multipole algorithm (LF-MLFMA). Accelerating iterative solutions using robust preconditioning techniques may not be sufficient to reduce the overall processing time when the ordinary high-frequency MLFMA is applied to metamaterial problems. The major bottleneck, i.e., the low-frequency breakdown, should be eliminated for efficient solutions. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Therefore, in addition to fast algorithms, preconditioning and stabilization techniques are required to ensure reliable solutions. Despite the challenging nature of the problems, some realistic metamaterials have been successfully analyzed via full-wave solvers, particularly those based on MLFMA [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to fast algorithms, preconditioning and stabilization techniques are required to ensure reliable solutions. Despite the challenging nature of the problems, some realistic metamaterials have been successfully analyzed via full-wave solvers, particularly those based on MLFMA [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surface integral equations (SIE) have been extensively used for solving scattering problems involving homogeneous or piecewise homogeneous dielectric objects [8][9][10][11][12][13][14][15]. Recent works have shown that their application may be extended to the homogeneous LHM analysis [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a significant amount of work has been devoted to design fast parallel algorithms that can reduce the O (n 2 ) computational complexity for the M-V product with boundary element equations, like the Fast Multipole Method (FMM) by V. Rokhlin [35], the H-matrix approach by W. Hackbush [25], the Adaptive Cross Approximation by M. Bebendorf [4], and other approaches. Since the pioneering work by Rokhlin and his co-authors, the Fast Multipole Algorithm continues to receive considerable attention in Electromagnetics, see e.g., [20,21,31,32,39].…”
Section: Introductionmentioning
confidence: 99%